2013
DOI: 10.1080/09581596.2013.827325
|View full text |Cite
|
Sign up to set email alerts
|

Toward stronger theory in critical public health: insights from debates surrounding posthumanism

Abstract: The "posthumanist turn" in critical theory comprises efforts to recognize and analyze the interdependence of human existence with non-human entities, including other animals, spaces, and technologies. Scholarship aligned to and debating posthumanism pertains to public health, but has yet to be clearly articulated for a public health audience. This commentary and an appended glossary illustrate the relevance of these ideas for enhancing critical theory in public health.2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 54 publications
(50 reference statements)
0
36
0
Order By: Relevance
“…It is within this cluster that a large number of publications can be found that conceptually reflect upon or empirically apply the 'One-health' paradigm. The two publications that explicitly use the terminology of posthumanism can also be found in this cluster (Rock, 2013;Rock, et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It is within this cluster that a large number of publications can be found that conceptually reflect upon or empirically apply the 'One-health' paradigm. The two publications that explicitly use the terminology of posthumanism can also be found in this cluster (Rock, 2013;Rock, et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Based on this analysis we consider how posthumanist theory could productively contribute to these areas of public health research into the future. This paper builds directly upon Melanie Rock, Chris Degeling and Gwendolyn Blue's (2014) argument that posthumanist theory is relevant for public health. Toward that end, Rock, Degeling and Blue have provided a synthetic review of the posthumanist literature, tracing it through post-structuralism generally and science and technology studies (STS) in particular.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent commentary Rock et al (2014) pull together diverse theoretical traditions including 'Actor Network Theory' (associated by the authors with Bruno Latour, Michel Callon and John Law) and the concept of 'enactment' (associated with Mol's book The Body Multiple). In her broader account of 'post anthropocentric thought ' Braidotti (2013) similarly draws heavily on STS though she makes more reference to feminist work associated with Donna Haraway, anthropologies of technology and Foucauldian studies of biopower under this heading.…”
Section: Introductionmentioning
confidence: 99%